2016
DOI: 10.1001/jamainternmed.2015.8260
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Short Message Service Text-Based Smoking Cessation Intervention Among University Students

Abstract: Importance Smoking is globally the most important preventable cause of ill health and death. Mobile telephone interventions and, in particular, short message service (SMS) text messaging, have the potential to overcome access barriers to traditional health services, not least among young people. Objective To determine the effectiveness of a text-based smoking cessation intervention among young people. Design, Setting, and Participants A single-blind, 2-arm, randomized clinical trial (Nicotine Exit [NEXit])… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
117
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 88 publications
(134 citation statements)
references
References 32 publications
4
117
0
2
Order By: Relevance
“…Using the BCT taxonomy suggested by Mitchie et al [10], which includes 43 BCTs previously found to be reliable in coding the context of smoking cessation interventions, the intervention used 32 different BCTs, for example: “provide information on consequences of smoking and smoking cessation”, “prompt review of goals”, and “boost motivation and self-efficacy”. Slightly more than half of the messages clearly combined more than one BCT [5] (see Table 1). As part of the formative development, 10 smoking cessation experts and 10 smokers evaluated and provided comments and suggestions on each message [4].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Using the BCT taxonomy suggested by Mitchie et al [10], which includes 43 BCTs previously found to be reliable in coding the context of smoking cessation interventions, the intervention used 32 different BCTs, for example: “provide information on consequences of smoking and smoking cessation”, “prompt review of goals”, and “boost motivation and self-efficacy”. Slightly more than half of the messages clearly combined more than one BCT [5] (see Table 1). As part of the formative development, 10 smoking cessation experts and 10 smokers evaluated and provided comments and suggestions on each message [4].…”
Section: Methodsmentioning
confidence: 99%
“…To address this, a text messaging-based smoking intervention, the NEXit intervention, was developed, aimed specifically at this group [4, 5]. A text messaging-based intervention was chosen because mobile phones are increasingly being used as a medium for reminders about medication and self-management of chronic diseases, such as diabetes, as well as behavioural change interventions on problematic drinking, obesity, tobacco cessation and sedentary lifestyle [69].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most agreed that the variation was valuable, particularly among those who reduced or stopped drinking. One possible conclusion also noted in previous research using a text messagingbased intervention among students who smoked may be that text message-based cessation interventions are more suitable for those who are motivated to use these types of programs, and those who are not fully motivated or not determined to change their lifestyle habits may find other types of support more suitable, for example face-to-face meetings with professionals [17].…”
Section: Discussionmentioning
confidence: 83%
“…Destaca que la mayoría de los estudios publicados sobre la efectividad de intervenciones desde teléfonos móviles han sido realizados vía mensajería de texto, dado el amplio uso de éstos en el tiempo en que fueron conducidos los estudios. Una revisión sistemática reciente demuestra un aumento en la abstinencia de consumo de tabaco a 6 meses usando telefonía móvil comparado con población control (RR 1,67 IC 95% 1,46 -1,9; GRADE moderado * ) 5 siendo efectiva en diversos contextos y poblaciones 6,8 . Dentro de las ventajas de la telefonía móvil se encuentra la posibilidad de alcanzar a sectores masivos de la población, su fácil acceso y familiaridad de los usuarios, así como la flexibilidad temporal y geográfica dado que las personas pueden acceder a ellas en el momento y lugar que estimen convenientes.…”
Section: La Mhealth Se Refiere Al Uso De Dispositivos Móviles Como Uunclassified